After-School Programs for Bilingual Students: Preservice Teachers' Perspectives and Students' Achievement. Issue 4 (19th July 2017) - Falk-Ross, Francine; Dealy, Ann; Porcelli, Justinna; Hammond, Jonna; Evans, Brian
ABSTRACT: We studied the process and products of developing effective tutoring programs to support Tier 2 bilingual students with a focus on teachers' perspectives and students' achievement to assess and teach students based on need. With the understanding that young students require individual attention to resolve specific misunderstandings, optimally without the distractions of surrounding classroom activity, after-school tutoring has propelled students forward in literacy and educational achievement. Tutoring programs can also serve as professional development opportunities for preservice and practicing teachers as they negotiate the balance between assessment and instruction for children's individual differences in learning. This mixed-methods study involved language-into-literacy experiences using a variety of reading passages and multimedia sources. Results indicated themes in teachers' changing approaches toward honoring language and literacy competencies of bilingual students and revealed statistically significant positive changes in students' literacy competencies.